2011
DOI: 10.1111/j.1399-0012.2009.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of CYP3A5 genotypes in dose requirements of tacrolimus and everolimus after heart transplantation

Abstract: We conclude that in adult patients after heart transplantation, CYP3A5 genotypes have a strong influence on Tacrolimus, but not Everolimus dose requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 14 publications
7
21
0
Order By: Relevance
“…Our results showed that the CYP3A5 expressors had significantly lower dose-adjusted TAC-C 0 concentrations compared with CYP3A5 nonexpressors at all studied time points requiring around 2.2-to 2.6-fold higher daily TAC doses to reach the targeted blood C 0 concentration. A similar effect of the CYP3A5*3 variant on TAC dose requirement has been shown also in the previous studies on HTx recipients, based on cohorts of 15 and 65 adult patients 21,28 and 37 and 54 pediatric patients. 11,22 This study, however, was the first to investigate the influence of the POR*28 variant on TAC and CSA dose requirement in HTx recipients.…”
Section: Discussionsupporting
confidence: 84%
“…Our results showed that the CYP3A5 expressors had significantly lower dose-adjusted TAC-C 0 concentrations compared with CYP3A5 nonexpressors at all studied time points requiring around 2.2-to 2.6-fold higher daily TAC doses to reach the targeted blood C 0 concentration. A similar effect of the CYP3A5*3 variant on TAC dose requirement has been shown also in the previous studies on HTx recipients, based on cohorts of 15 and 65 adult patients 21,28 and 37 and 54 pediatric patients. 11,22 This study, however, was the first to investigate the influence of the POR*28 variant on TAC and CSA dose requirement in HTx recipients.…”
Section: Discussionsupporting
confidence: 84%
“…Several groups have previously reported the effects of these polymorphisms on tacrolimus metabolism, which results in higher dose requirements and significant delays in achieving target blood concentrations (12)(13)(14)(15)(16)(17). This may predispose kidney allograft recipients to acute rejection (AR), as lower tacrolimus concentrations at early stages after transplantation are associated with AR (18).…”
mentioning
confidence: 96%
“…11,14–18,2023,55 In pediatric renal transplant patients, CYP3A5 * 1 was associated with lower tacrolimus serum concentration despite therapeutic drug monitoring, perhaps due to clinician hesitancy to prescribe the high doses of tacrolimus required in these patients. 17,18 Through PREDICT, clinical CYP3A5 genotyping is available for both pediatric and adult patients receiving tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Functional CYP3A alleles have been associated with more rapid tacrolimus inactivation and higher dose requirements in pediatric renal transplant patients 1621 and adult cardiac transplant patients. 22,23 The most well characterized CYP3A variant is CYP3A5 * 3 , which includes a splicing variant that prevents translation of active enzyme. One or more copies of the functional enzyme (encoded by CYP3A5 * 1 ) are present in the majority of African-American individuals, but homozygosity for the non-functional genotype, denoted by CYP3A5 * 3/ * 3 , is more common among individuals of European and Asian descent and Hispanic Americans.…”
Section: Maintenance Immunosuppressive Agents In Pediatric Cardiac Trmentioning
confidence: 99%
See 1 more Smart Citation